2020
DOI: 10.1259/dmfr.20190347
|View full text |Cite
|
Sign up to set email alerts
|

Validity of micro-CT for in vitro caries detection: a systematic review and meta-analysis

Abstract: Objective: To investigate the validity of micro-CT for in vitro caries detection in comparison with histology as the reference standard. Methods: A systematic search was conducted in the databases Latin American and Caribbean Health Sciences (LILACS), LIVIVO, PubMed, Scopus and Web of Science from their inception to 16 January 2019. Grey literature was searched on Open Grey, ProQuest Dissertations and Theses Database and Google Scholar. In vitro studies assessing the validity of micro-CT for caries detection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Thus, Although histological processing and analysis is still used as a gold standard for dental caries detection, it is fundamentally a destructive method because it requires sectioning of the sample for microscopic examination. Therefore, the micro-CT technique used as the golden standard in the present study has been recently proposed and validated to define caries severity under laboratory conditions [13,14,24,25],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Although histological processing and analysis is still used as a gold standard for dental caries detection, it is fundamentally a destructive method because it requires sectioning of the sample for microscopic examination. Therefore, the micro-CT technique used as the golden standard in the present study has been recently proposed and validated to define caries severity under laboratory conditions [13,14,24,25],…”
Section: Discussionmentioning
confidence: 99%
“…To measure the sensitivity, specificity, and accuracy of digital diagnostic alternatives for caries, a micro-CT technique has been proposed as a gold standard to validate caries severity under laboratory conditions [13,14], especially because histological methods have low accuracy in detecting the real depth of dentin lesions [15]. Thus, the aim of the present ex vivo study was to compare the agreement on caries diagnosis and treatment decisions of occlusal surfaces images of permanent carious teeth obtained by SoproLife ® , in white light and fluorescence mode, and digital radiographs, against a micro-CT gold standard.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-computed tomography was used to confirm the formation of subsurface lesions that would be like clinically detected WSLs. This is a validated method for detecting subsurface lesions ( Oliveira et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The total volume of the demineralization solution used was determined using the following formula: Using this volume of similar demineralization solutions results in an almost 43 µm deep subsurface lesion ( Magalhães et al, 2009 ). The establishment of sub-enamel demineralized lesions on each tooth’s exposed buccal and lingual surfaces was validated using micro-computed tomography (SkyScan 1172; Kontich, Belgium) ( Oliveira et al, 2020 ). Figure 1 shows a micro-CT image of the artificial WSLs created.…”
Section: Methodsmentioning
confidence: 99%
“…To validate the information provided by SD-OCT, a representative image of each group was obtained by micro-CT, a sensitive method to detect early lesions produced in vitro [Hamba et al, 2012] and the reference standard for the analysis of proximal enamel surfaces [Oliveira et al, 2020]. The selected micro-CT images confirmed that a demineralized surface area was detectable.…”
Section: Discussionmentioning
confidence: 99%